Should Indonesia adopt a Stewardship Code? - Mangunsong, Nathaniel O L; Dewi, Yetty Komalasari (University of Jember, 2025)
Shareholder stewardship has rapidly become a popular concept among policymakers, companies, and investors around the world. On its first release in 2010, the inaugural United Kingdom stewardship code was primarily targeted to incentivize institutional investors to be actively engaged as “stewards” in the corporate governance of companies in which they are shareholders. In Southeast Asia, Singapore has adopted separate stewardship codes for institutional investors and family companies. This article aims to explore if Indonesia should adopt a Stewardship Code like the above codes in Singapore and, if yes, how these codes should be adopted in Indonesia.KEYWORDS: Shareholder stewardship, Stewardship code, Corporate governance.